Factors influence OSH acceptance in Kencana Torsco Sdn Bhd, Sitiawan, Perak - Dinesh Kumar, K. Krishnan (2013)
This research paper presents the success factor in the acceptance towards Occupational Safety and Health (OSH). OSH acceptance among human being can be varies among us and be influenced with certain factors. However, the study is to identify which factors that influences most in the success of Safety and Health in an organization. There are many sectors in Malaysia that are actually not really fully complying towards our Occupational safety and Health Act (OSHA) 1994 that can lead to many serious workplace incident and fatality as well. OSH is big terms that represent the company’s backbone. The weak and strength of OSH in an organization will define the strength and weak the organization will be. Furthermore, OSH cannot move alone by itself, therefore the success of OSH at a workplace can be seen if there is two parties make the same approach and responsibilities that enable the OSH become more effective. This is all about management commitment and employees acceptance and support towards OSH. Therefore the objective of this paper is to find out what are the needs to improve OSH in the organization that are influenced by human factor